2020
DOI: 10.1111/idj.12535
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral health status and chronic obstructive pulmonary disease in Korean adults

Abstract: Objectives: This study aimed to elucidate the association between oral health status and chronic obstructive pulmonary disease (COPD) in Korean adults (≥ 40 years old) using a representative national dataset from the 6th Korea National Health and Nutrition Examination Survey (6th KNHANES, 2013-2015. Methods: Participants aged ≥ 40 years from the 6th KNHANES who had received an oral and pulmonary function tests (N = 7719) were included in this study. The participant characteristics according to COPD were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Also, other chronic diseases that can have detrimental effects on oral health were present such as dementia (14%), obstructive lung diseases (13%) and rheumatoid arthritis (6%) whereas 50% presented with moderate to low renal function. Previous studies 55 , 56 have reported an association between missing teeth and COPD, which was also found in this study. We found a significant association between COPD in the dentate patients and the presence of fewer than 20 teeth or a DFT of over the mean, (p = value 0.019 and 0.048 respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Also, other chronic diseases that can have detrimental effects on oral health were present such as dementia (14%), obstructive lung diseases (13%) and rheumatoid arthritis (6%) whereas 50% presented with moderate to low renal function. Previous studies 55 , 56 have reported an association between missing teeth and COPD, which was also found in this study. We found a significant association between COPD in the dentate patients and the presence of fewer than 20 teeth or a DFT of over the mean, (p = value 0.019 and 0.048 respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, some other studies 23,24,40 showed that there was no significant association between periodontitis and airflow obstruction. Jung et al 24 stated that the periodontal status was not significantly associated with COPD. A crosssectional evaluation conducted by Lee et al 23 indicated that the risk of periodontitis was not significantly associated with lung function.…”
Section: Discussionmentioning
confidence: 95%
“…The results of linear regression showed a negative correlation between periodontitis and FEV1, FVC, and FEV1/FVC, which were consistent with the results of logistic regression analysis in the study. Nevertheless, some other studies 23,24,40 showed that there was no significant association between periodontitis and airflow obstruction. Jung et al 24 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations